2020
DOI: 10.1097/01.ogx.0000659624.79175.0c
|View full text |Cite
|
Sign up to set email alerts
|

How Women Are Treated During Facility-Based Childbirth in Four Countries: A Cross-sectional Study With Labour Observations and Community-Based Surveys

Abstract: Background Women across the world are mistreated during childbirth. We aimed to develop and implement evidenceinformed, validated tools to measure mistreatment during childbirth, and report results from a cross-sectional study in four low-income and middle-income countries. MethodsWe prospectively recruited women aged at least 15 years in twelve health facilities (three per country) in Ghana, Guinea, Myanmar, and Nigeria between Sept 19, 2016, and Jan 18, 2018. Continuous observations of labour and childbirth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 25 publications
(29 reference statements)
3
48
1
2
Order By: Relevance
“…In Pokhara Hospital, women having caesareans are less likely to share a bed and are monitored more closely in the immediate postnatal period, which may also contribute to an increased feeling of satisfaction with standards of care. In many settings, higher socio-economic status is associated with both a higher prevalence of caesarean section and more respectful care [17]. Measurement tools for RMNC clearly require validation at a local level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Pokhara Hospital, women having caesareans are less likely to share a bed and are monitored more closely in the immediate postnatal period, which may also contribute to an increased feeling of satisfaction with standards of care. In many settings, higher socio-economic status is associated with both a higher prevalence of caesarean section and more respectful care [17]. Measurement tools for RMNC clearly require validation at a local level.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in the last decade have highlighted mistreatment of women during labour in LMICs [12][13][14], including physical and verbal abuse, discrimination based on maternal age (young or elderly), and ethnicity or social class [15,16]. Other manifestations of mistreatment included the provision of care without consent, obstructing the presence of a birth companion, and withholding food during labour without the woman's consent or a clinical indication [15,17]. In contrast, respectful care is synonymous with a positive user experience and should include women and families as active-participants throughout pregnancy and childbirth [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, another study in rural northern Ghana revealed that midwives lack beds to provide maternity services for women admitted to the health facilities [22]. Due to lack of suitable beds (do not have the necessary bed accessories such as side rails), some women in the current study were managed on the oor and this act is observed in resource constraint settings, where women would have to share beds with other women during and after childbirth or even nursed on the oor [23]. In this study, the midwives indicated that in instances where the beds had no side rails, family relatives were invited to sit by the side of the patient to prevent falls due to eclamptic seizures.…”
Section: Discussionmentioning
confidence: 89%
“…Another possible mechanism is that RMC training helps reduce discrimination and stigma that may otherwise lead to inequitable quality of care. Studies have noted that women of younger age and lower education experience higher levels of disrespect and abuse during labor and delivery [36]. In Afghanistan, qualitative research has demonstrated that respectful maternity care is a gap that must be addressed [13,17].…”
Section: Discussionmentioning
confidence: 99%